2011
DOI: 10.1016/j.ijhcs.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Pushing personhood into place: Situating media in rural knowledge in Africa

Abstract: Designing interactions with technologies that are compatible with rural wisdom and skills can help to digitally enfranchise rural people and, thus, contribute to community cohesion in the face of Africa's urbanization. Oral information has been integral to rural identity and livelihood in Africa for generations. However, the use of technology can inadvertently displace the knowledge of communities with practices that differ from the knowledge traditions in which technology is designed. We propose that devices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 24 publications
3
66
0
3
Order By: Relevance
“…The open card sorting method supported the discovery of a new categorization scheme which we call location-relational. The pattern confirms prior research on Herero's prioritization of place as a meaningful location with activities and protocols attached to [13]. The findings dramatically changes our previous design ideas and future retrieval of interface objects will follow this new categorization scheme for ensuring intuitiveness and preservation of tacit knowledge in the interface.…”
Section: Resultssupporting
confidence: 81%
“…The open card sorting method supported the discovery of a new categorization scheme which we call location-relational. The pattern confirms prior research on Herero's prioritization of place as a meaningful location with activities and protocols attached to [13]. The findings dramatically changes our previous design ideas and future retrieval of interface objects will follow this new categorization scheme for ensuring intuitiveness and preservation of tacit knowledge in the interface.…”
Section: Resultssupporting
confidence: 81%
“…The tablet's portability meant audio files trace spatial patterns such as pauses and sounds recorded along topokinetic paths when a person carried the tablet from one to the next in meetings and indications of the relative orientations of recorders and speakers. We have reported associations between bodies, utterances, spatiality and social relations in sense-making elsewhere in rural Africa [8], and we found that certain meanings emerge in Mankosi when gestures, social roles and the spatial arrangement of photos combined.…”
Section: New Sensitivities In Designing For Oral Usersmentioning
confidence: 65%
“…discussions of the phenomenon (Rooney, 2005;Lin, 2006;Anyanwu, 2012); information & communication technologies (Butcher, 2011); education (Amavilah, 2009a;Ford, 2007;Weber, 2011;Wantchekon et al, 2014); institutional regime & economic incentives (Letiche, 2006;Cogburn, 2003;Andrés & Asongu, 2013); intellectual capital & economic development (Wagiciengo & Belal, 2012;Preece, 2013); innovation (Oyelaran-Oyeyinka & Sampath, 2007;Carisle et al, 2013); research & development ( Sumberg, 2005;German & Stroud, 2007); indigenous knowledge systems (Lwoga et al, 2010;Raseroka, 2008); KE in the transformation of space (Moodley, 2003;Maswera et al, 2008); intellectual property rights (Lor & Britz, 2005;Zerbe, 2005;Andrés & Asongu, 2013;Myburgh, 2011;Andrés et al, 2014); and spatiality in the production of knowledge (Bidwell et al, 2011;Neimark, 2012) .…”
Section: Introductionmentioning
confidence: 99%